Rantau and Minangkabau Women: A Global View of the Postcolonial Feminist Perspective - Fatimah, Siti (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
Discussing the greatness of the Minangkabau ethnic group globally, almost every expert always connects it with the migration culture of the Minangkabau people. Historical facts reveal that merantau is synonymous with men or the patriarchal world. It is a paradox with the kinship system adopted by the Minangkabau society, which is matrilineal and matriarchal. This paper aims to: (1). Reveal the place of women in the Minangkabau migration culture; (2). This research uses the historical method combined with the literature method. This article is supported by the oral history method to sharpen the analysis. This approach is similar to the interview method in qualitative research, which consists of surveys of those who are active and experienced in implementing the Minangkabau tradition. They are analysing the global view of the postcolonial perspective in the Minangkabau people's migration culture. This study uses the historical method combined with the literature method. The results of this study indicate that the matrilineal culture of the Minangkabau people in the colonial period was very thick with patriarchal perspectives and gender bias. Unlike the postcolonial period, there was a significant paradigm shift and historical reality. During the postcolonial period, Minangkabau women were allowed to migrate to develop their potential in the public sphere.